Two‐step technique of early adrenal artery ligation in open adrenalectomy of giant right adrenal pheochromocytomas: Three case reports. Issue 1 (12th November 2018) - Ochi, Atsuhiko; Fan, Bo; Kimura, Natsuo; Watanabe, Hisaki; Toki, Sari; Fukuokaya, Wataru; Okada, Daigo; Aikawa, Koichi; Huang, Tingwen; Suzuki, Koichiro; Shiga, Naoki; Kitagawa, Yasuhide; et al.
Abstract : Introduction: Surgical manipulation of a pheochromocytoma carries the risk of releasing catecholamines into bloodstream leading to severe intraoperative hypertension. Case presentation: We present three patients with right adrenal pheochromocytoma over 10 cm diameter: a 40‐year‐old woman, 63‐year‐old man, and 66‐year‐old woman. They were diagnosed by 123I‐MIBG scintigraphy and received preoperative antihypertensive treatment with 16 mg/day of doxazosin. Open adrenalectomy was performed with early right adrenal artery ligation between the inferior vena cava and ventral aorta (Step 1) as well as between the tumor and upper pole of the right kidney (Step 2). There was no severe intraoperative hypertension, and no recurrence was observed over 33 months, postoperatively. Conclusion: Early adrenal artery ligation may stop tumor blood supply and significantly reduce the catecholamine release. Our technique was thought to be safe and useful for preventing severe intraoperative hypertension in giant right adrenal pheochromocytoma.